Global Englishes and the Semiotics of German Radio—Encouraging the Listener's Visual Imagination Through Translingual and Transmodal Practices - Schaefer, Sarah Josefine (Frontiers in Communication, 2022)
Due to increasing mediatisation of societies and the global diffusion of English, previous research has paid a great deal of attention to the use of English in contact with other linguistic resources. Traditionally, the focus in studies on global Englishes is predominantly on verbal resources, which are often examined in media corpora. The recent paradigmatic shift towards a conceptualisation of language as a social practice, however, also acknowledges other resources such as music, images and sounds as part of semiotic assemblages in the process of meaning-making. This paper contributes to this current debate and argues for a more holistic view on language illustrated by examples of the use of global Englishes in German radio media texts. The examples show the complexities of translingual and transmodal practices in mass media communication and how English linguistic resources are deeply entangled with other semiotic resources and thereby locally appropriated in semiotic assemblages to stimulate the listener's visual imagination and achieve communicative success in a non-visual medium.